Estudo histológico comparativo entre dois métodos de obtenção de cortes de alvéolos de ratos. - Okamoto, T.; Vasconcelos Fialho, A. C. (My University, 1990)
The chronology of the wound healing process following tooth extraction was studied by means of two kinds of histological cuts. Two groups of 42 albino rats were employed. In the first one, the sockets were cut in a transversal way. In the second one the cuts were performed in a longitudinal way. The rats were sacrificed after 3, 6, 9, 15, 21, 24, and 28 days following the surgeries. After laboratorial outline the obtained pieces were stained by hematoxylin and eosin for histological purposes. It way be concluded that: 1. The results got from longitudinal cuts were in agreement to those described by other authors; 2. The transversal cuts allow us to detect intensive resorption of the lateral alveolar wall at the cervical thirs; 3. On the 21st day following dental extraction the incisor socket of the rat shows a great deal of areas not ossified; 4. The healing process of dental extraction wounds of the upper incisor of the rat is completed between 24 and 28 post operative days.
Comparative histological study of two methods of obtaining alveolar sections in rats
Keywords: animal; comparative study; histology; osteolysis; rat; rat strain; tooth extraction; wound healing; Alveolar Bone Loss; Animal; Comparative Study; English Abstract; Histological Techniques; Rats; Rats, Inbred Strains; Support, Non-U.S. Gov't; Tooth Extraction; Wound Healing